Photocatalytic degradation of organic pollutant using visible active - boron doped photocatalyst - Md Noor, Ariffin; Mostafa, Tarek; Khan, Maksudur R. (IOP Publishing, 2021)
Boron-doped TiO2 (B-TiO2) nanocatalysts were prepared by the sol-gel method, characterized by X-Ray diffraction (XRD) and diffusive reflectance UV-vis spectroscopy (DRS). XRD results exhibited that the doping of boron element could potentially inhibit the growth of grain and promote the formation of anatase phase and diboron trioxide phase. The photocatalytic activity of the B-TiO2 nanophotocatalyst was evaluated by the degradation test on one of the most widely used organic dyes, methylene blue (MB). The result indicated the doped B-TiO2, with 0.25g/L catalyst loading, were more active than the undoped TiO2 in breaking down the MB. The maximum conversion of MB by the doped TiO2 was 80.60%, approximately 14% higher than the pristine TiO2. The as-synthesized B-TiO2 was calcined at 450°C demonstrated higher photocatalytic activity than undoped TiO2 after 240mins of visible light illumination.